2011
DOI: 10.1016/j.earscirev.2011.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean water resources in a global change scenario

Abstract: Mediterranean areas of both southern Europe and North Africa are subject to dramatic changes that will affect the sustainability, quantity, quality, and management of water resources. Most climate models forecast an increase in temperature and a decrease in precipitation at the end of the 21st century. This will enhance stress on natural forests and shrubs, and will result in more water consumption, evapotranspiration, and probably interception, which will affect the surface water balance and the partitioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
390
1
27

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 765 publications
(472 citation statements)
references
References 281 publications
13
390
1
27
Order By: Relevance
“…With growing populations and increasingly arid conditions in the future, water reuse is bound to become more important in North Africa and the Middle East. 15,18,51 Additional incentives are (i) the cost, which is approximately half that of creating usable water by desalination plants, 51 and (ii) the recovery of P and N, under the form of biosolids, sludge and wastewater itself, which can be used as fertilizer for agricultural production. The latter also represents a mitigation measure to deal with the projected depletion of P mining reserves within the next 50−400 years.…”
Section: Discussionmentioning
confidence: 99%
“…With growing populations and increasingly arid conditions in the future, water reuse is bound to become more important in North Africa and the Middle East. 15,18,51 Additional incentives are (i) the cost, which is approximately half that of creating usable water by desalination plants, 51 and (ii) the recovery of P and N, under the form of biosolids, sludge and wastewater itself, which can be used as fertilizer for agricultural production. The latter also represents a mitigation measure to deal with the projected depletion of P mining reserves within the next 50−400 years.…”
Section: Discussionmentioning
confidence: 99%
“…Various authors have reported that land-cover expansion or contraction at the watershed scale affects water resources by increasing or decreasing evapotranspiration and, hence, altering streamflow production (Boch and Hewlett 1982, Matheussen et al 2000, Delgado et al 2010, García et al 2011. In this context, seasonal variation of evapotranspiration has been observed with land-cover change (Dunn and Mackay 1995, Olchev et al 2008, Nosetto et al 2011, although the effects on runoff would occur only during summertime, when plants increase their water 274 284 294 304 314 324 334 344 354 364 9 19 29 39 49 59 69 79 89 99 109 119 129 139 149 159 169 179 189 199 209 219 229 239 249 259 275 285 295 305 315 325 335 345 355 365 9 19 29 39 49 59 69 79 89 99 109 119 129 139 149 159 169 179 189 199 209 219 229 239 249 259 demand, particularly in transitions between tree-and herbaceous-dominated covers.…”
Section: Long-term Dynamicsmentioning
confidence: 99%
“…The studies of rainfall, discharge, sediment transport and runoff-and sediment-contributing areas, are extremely important in interpreting the spatial and temporal dynamics in terms of quantity and quality of water resources (Lindim et al 2011). In this context, water resources are yielded primarily by headwaters situated in mountainous zones that are continuously perturbed by major changes in land use, which have a farreaching impact on reservoir management (López et al 2004, García et al 2011. For most European Mediterranean watersheds, the relationships among precipitation, discharge and suspended sediment during flood events are complex, hindering the formulation of predictive hydrological and sedimentological models.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, and since climate models predict less rainfall between 2040 and 2070 than between 1960and 1990(García-Ruiz et al 2011, such areas will be especially vulnerable to the impacts of climate change. Indeed, the decrease in rainfall is expected to reduce aquifer recharge.…”
Section: Introductionmentioning
confidence: 99%